2022
DOI: 10.1021/acschemneuro.1c00699
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the MAGL/FAAH Dual Inhibitor JZL-195 on Streptozotocin-Induced Alzheimer’s Disease-like Sporadic Dementia in Mice with an Emphasis on Aβ, HSP-70, Neuroinflammation, and Oxidative Stress

Abstract: Alzheimer's disease is identified by pathological hallmarks such as intracellular neurofibrillary tangles (NFTs) and extracellular amyloid β plaques. Several hypotheses exist to define the neurodegeneration including microglial activation associated with neuroinflammatory processes. Recently, pharmacological inhibition of endocannabinoid (eCB)-degrading enzymes, fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL), is being investigated to modulate the pathology of Alzheimer's disease. While MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 91 publications
2
5
0
Order By: Relevance
“…Several investigators have demonstrated that 2-AG can be metabolized to 2-arachidonoyl LPA (herein named 2-AGP), a selective ligand of LPA1R ( Kanoh et al, 1986 ; Shim et al, 1989 ; Nakane et al, 2002 ), which modulates synaptic plasticity, Tau phosphorylation and cognitive function ( Castilla-Ortega et al, 2011 ; Roza et al, 2019 ). Our data report elevation of 2-AGP in CSF and plasma of AD patients in agreement with recent findings that indicate the failure of cognitive improvement after JZL-195 pharmacological inhibition of MAGL and FAAH activities in mouse model of AD ( Bajaj et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Several investigators have demonstrated that 2-AG can be metabolized to 2-arachidonoyl LPA (herein named 2-AGP), a selective ligand of LPA1R ( Kanoh et al, 1986 ; Shim et al, 1989 ; Nakane et al, 2002 ), which modulates synaptic plasticity, Tau phosphorylation and cognitive function ( Castilla-Ortega et al, 2011 ; Roza et al, 2019 ). Our data report elevation of 2-AGP in CSF and plasma of AD patients in agreement with recent findings that indicate the failure of cognitive improvement after JZL-195 pharmacological inhibition of MAGL and FAAH activities in mouse model of AD ( Bajaj et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…For example, we observe that putatively damaging bi-allelic variation in FAAH, a fatty acid amide hydrolase 37 , are associated with increased risk of dementia (log 10 (OR) = 22.92 (12.35−33.48), 𝑃 = 1.06×10 −5 ), consequently offering evidence supporting the hypothesis that lipid metabolism dysfunction is central to dementia pathogenesis 38 .…”
Section: Systematic Evaluation Of Bi-allelic Effects On Common Diseasesupporting
confidence: 56%
“…156 In contrast, inhibitors of endocannabinoid synthesis reduced amyloid-β load and neuroinflammation but failed to improve cognition. 157 In the clinic, ligands of Cannabinoid receptors are currently tested as neuromodulators to influence the behavioral and psychological symptoms in subjects with AD (NCT02351882). Additionally, gene therapy with recombinant BDNF is currently assessed in a phase 1 trial including people affected with AD and mild cognitive impairment to reduce neurodegeneration and rebuild synapses (NCT05040217).…”
Section: Target the Cellsmentioning
confidence: 99%
“…In preclinical models of AD, recombinant BDNF infusion reverted cognitive decline without altering the amyloid-β load (151). In contrast, inhibitors of endocannabinoid synthesis reduced amyloid-β load and neuroinflammation but failed to improve cognition (152). In the clinic, ligands of Cannabinoid receptors are currently tested as neuromodulators to influence the behavioral and psychological symptoms in subjects with AD (NCT02351882).…”
Section: Target the Cellsmentioning
confidence: 99%